Anecdotal Storytelling in the Adult ESOL and Literacy Classroom - Sarah Telfer; Daniela Bacova (Educational Futures, 2018)
This study investigates how anecdotal stories were used as a pedagogic tool in the teaching practice of trainee ESOL and literacy teachers. It analyses how trainees utilised anecdotal storytelling to enhance a ‘participatory’ approach to ESOL/literacy teaching. The data was collected in the form of short reflective posts written by the trainee teachers and uploaded on a Virtual Learning platform. The analysis focuses on the posts describing the features, uses and purposes of anecdotes used in the ESOL/literacy classroom. It provides a theoretical framework capturing the form, content, and primary and secondary functions of anecdotal storytelling.